Relics of possible (Mg,Fe)3Si2O7 and (Mg,Fe)4Si3O10: potential messengers from the Earth’s mantle - Simonpietro Di Pierro; Edwin Gnos; Damien Jacob; Bertrand Devouard; Hugues Leroux; Pascal Roussel (Physics and Chemistry of Minerals, 2026)

Seawater corrosive engineering assisted in-situ room temperature synthesis of Ni/Co/Fe trimetallic composition to achieve polyester plastics upgrading and green hydrogen production - Zhao-Hui Zhang; Zhi-Ran Yu; Yi Zhang; Alexandre Barras; Ahmed Addad; Pascal Roussel; Long-Cheng Tang; Sabine Szunerits; Rabah Boukherroub (Chemical Engineering Journal, 2024)

Listeria monocytogenes prevalence and genomic diversity along the pig and pork production chain - Jean Lagarde; Carole Feurer; Martine Denis; Pierre-Emmanuel Douarre; Pascal Piveteau; Sophie Roussel (Food Microbiology, 2024)

Ferrocene-based nitroheterocyclic sulfonylhydrazones: design, synthesis, characterization and trypanocidal properties - Miguel Gallardo; Rodrigo Arancibia; Claudio Jiménez; Shane Wilkinson; Patricia M. Toro; Pascal Roussel; Natacha Henry (JBIC Journal of Biological Inorganic Chemistry, 2023)

Ultimate mechanical properties of enstatite - Karine Gouriet; Pascal Roussel; Philippe Carrez; Patrick Cordier (Physics and Chemistry of Minerals, 2022)
The ultimate mechanical properties of MgSiO 3 orthoenstatite (OEN), as characterized here by the ideal strengths, have been calculated under tensile and shear loadings using first-principles calculations. Both ideal tensile strength (ITS) and shear strength (ISS) are computed by applying homogeneous strain increments along high-symmetry directions ([100], [010], and [001]) and low index shear planes ((100), (010), and (001)) of the orthorhombic lattice. We show that the ultimate mechanical properties of OEN are highly anisotropic during tensile loading, with ITS ranging from 4.5 GPa along [001] to 8.7 GPa along [100], and quite isotropic during the shear loading with ISS ranging from 7.4 to 8.9 GPa. During tensile test along [100] and [001], a modified structure close to OEN has been found. This modified structure is more stable than OEN under stress (or strain). We have characterized its elastic and ultimate properties under tensile loading. With ITS ranging from 7.6 GPa along [010] to 25.6 GPa along [001], this modified structure appears to be very anisotropic with exceptional strength along [001].

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

A Framework to Predict the Impacts of Shale Gas Infrastructures on the Forest Fragmentation of an Agroforest Region - Alexandre Racicot; Véronique Babin-Roussel; Jean-François Dauphinais; Jean-Sébastien Joly; Pascal Noël; Claude Lavoie (Environmental Management, 2014)

Stable isotope analyses on archived fish scales reveal the long‐term effect of nitrogen loads on carbon cycling in rivers - Jean‐Marc Roussel; Charles Perrier; Jaakko Erkinaro; Eero Niemelä; Richard A. Cunjak; Dominique Huteau; Pascal Riera (Global Change Biology, 2014)
Stable isotope analysis of organic matter in sediment records has long been used to track historical changes in productivity and carbon cycling in marine and lacustrine ecosystems. While flow dynamics preclude stratigraphic measurements of riverine sediments, such retrospective analysis is important for understanding biogeochemical cycling in running waters. Unique collections of riverine fish scales were used to analyse δ 15 N and δ 13 C variations in the food web of two European rivers that experience different degrees of anthropogenic pressure. Over the past four decades, dissolved inorganic N loading remained low and constant in the Teno River (70°N, Finland); in contrast, N loading increased fourfold in the Scorff River (47°N, France) over the same period. Archived scales of Atlantic salmon parr, a riverine life‐stage that feeds on aquatic invertebrates, revealed high δ 15 N values in the Scorff River reflecting anthropogenic N inputs to that riverine environment. A strong correlation between dissolved inorganic N loads and δ 13 C values in fish scales was observed in the Scorff River, whereas no trend was found in the Teno River. This result suggests that anthropogenic N‐nutrients enhanced atmospheric C uptake by primary producers and its transfer to fish. Our results illustrate for the first time that, as for lakes and marine ecosystems, historical changes in anthropogenic N loading can affect C cycling in riverine food webs, and confirm the long‐term interactions between N and C biogeochemical cycles in running waters.

Nucleolus: the fascinating nuclear body - Valentina Sirri; Silvio Urcuqui-Inchima; Pascal Roussel; Danièle Hernandez-Verdun (Histochemistry and Cell Biology, 2008)

Molecular Mechanisms of the Adsorption of a Model Protein (Human Serum Albumin) on Poly(Methylidene Malonate 2.1.2) Nanoparticles - Yoléne Bousquet; Pieter J. Swart; Nathalie Schmitt-Colin; Florence Velge-Roussel; Mirjam E. Kuipers; Dirk K. F. Meijer; Nicole Bru; Johan Hoebeke; Pascal Breton (Pharmaceutical Research, 1999)